RANCANG BANGUN ROBOT PEMADAM API BERODA FOUR WHEEL DRIVE (4WD) BERBASIS KENDALI LOGIKA FUZZY - ., Muhammad Yasyfi (Faculty of Engineering, Universitas Tanjungpura, 2017)
Progress in technology and robotic caused by the large number of research and also by uses in daily life. There are many methods in robotics control where one of them is fuzzy logic control .One of them that uses the Fuzzy Logic control is the fire extinguisher wheeled four wheel drive ( 4wd ) robot. Where the fuzzy logic control is used to get 4 pieces motor’s Output from 5 pieces input by reading the distance from ultrasonic sensors. By using Arduino Due as microcontroller with quickly speed to data processing, so that can process and calculate 79 rule set in this robot. With the use of 4WD allowed the robots to traverse the uneven as incline as well as by mamdani’s fuzzy logic control, robots can quickly to find a fire, turn off the fire, and back to the starting point with the 100 % the success rate of 15 times experiments with the fastest is 30 seconds on speed average 33,47 seconds u sing fuzzy logic control which tis faster than not using fuzzy logic who has only the fastest speed is 32 seconds speed’s average 35,73 seconds .Keyword: 4WD Fire Exthinguish Robot, Arduino Due, Fuzzy Logic.